Toward integrative communicative competence: Linguistic and intercultural needs of tour guide trainees - Amalia Ilmi Fitriyanti; Joko Priyana; Yeni Artanti; Agwin Degaf (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2026)
The objective of this study is to identify the linguistic and intercultural needs of tour guide trainees as a foundation for developing integrative communicative competence through English for Specific Purposes (ESP) materials that promote intercultural awareness. The trainees, who are currently at the A1 proficiency level, exhibit a rudimentary understanding of the intercultural aspects pertinent to tourists. This deficiency manifests in a conspicuous lack of self-assurance and proficiency in English communication. This case prompted an analysis of their specific learning needs. A qualitative case study was conducted, involving 23 trainees and one senior tour guide at Prambanan Temple. Data were collected through questionnaires and interviews. The findings indicate that the primary need for trainees is the development of effective communication skills, particularly in listening and speaking, through materials that integrate linguistic competence and intercultural awareness. The analysis identified grammar and pronunciation as the most essential linguistic elements, while intercultural communication was deemed the most crucial cultural aspect. Consequently, ESP materials for tour guides should integrate B1-level English proficiency with intercultural understanding to prepare them for effective professional communication in global tourism contexts.